Access and Equity in Ontario Teacher Education: Teacher Candidates’ Perceptions - Holden, Michael; Kitchen, Julian (Alberta Journal of Educational Research, 2019)
Access, equity, and equitable representation are ongoing challenges in teacher education. While many Canadian teacher education programs identify equity and diversity as key values, these values do not always result in rates of representation that reflect the student population. Minoritized teacher candidates also experience our programs in unique ways, creating gaps between university equity statements and the lived experiences of our students. This study therefore examines the perspectives of 13 teacher candidates who self-identify as members of various underrepresented groups. Participants’ experiences offer key insights into the challenge of achieving equitable and diverse representation. The presented findings will be of interest to teacher educators and other stakeholders committed to addressing the complex task of increasing equity and access for underrepresented groups in their programs. L’accès, l’équité et la représentation équitable constituent des défis constants en formation des enseignants. Alors que plusieurs programmes de formation des enseignants identifient comme valeurs fondamentales l’équité et la diversité, l’adoption de ces valeurs ne mène pas toujours à des taux de représentation qui reflètent la population des étudiants. Les candidats minoritaires au programme de formation à l’enseignement vivent l’expérience du programme différemment, ce qui crée des écarts entre l’énoncé de l’université sur l’équité et le vécu des étudiants. Cette étude porte sur la perspective de 13 étudiants candidats au programme de formation à l’enseignement qui s’auto-identifient comme membres de divers groupes sous-représentés. Ces expériences offrent des aperçus essentiels sur le défi d’atteindre une représentation équitable et diverse. Les résultats sauront intéresser les formateurs d’enseignants et d’autres parties prenantes qui s’engagent à aborder la tâche complexe qui est celle d’augmenter l’équité et l’accès à leurs programmes pour les étudiants sous-représentés. Mots clés : accès; équité; formation des enseignants; groupes sous-représentés; admissions